Sosialisasi dan Strategi Perlindungan Anak Terpadu Berbasis Masyarakat di Kelurahan Bantar Gebang dan Cikiwul - Rina Sovianti; Novrian (Jurnal Pengabdian Kepada Masyarakat Kalam, 2022)
The challenge in preventing violence against children in society is the failure of laws that prohibit all forms of violence against children, the law is silent, and its enforcement is often inadequate. Likewise, social attitudes and cultural practices forgiving violence against children, lack of knowledge about good parenting patterns, legal knowledge about violence against children, understanding and causes of violence against children.Until March 2021, there were 40 reports of cases of violence against children and women in Bekasi City (2), by looking at these data, it is necessary to carry out community-based child protection socialization at the sub-district level in Bekasi City.Cases of sexual violence against children still dominate in Bekasi City compared to other cases. The Bekasi City Women and Children Protection Empowerment Service (DPPPA) stated that even out of 75 cases of child violence handled from January to July 2019, around 30 percent were sexual crimes against children. The perpetrator is the closest person to the victim's family.The method of implementing community service is through socialization to cadres in Bantar Gebang and Cikiwul Villages for the next cadres to continue to the community in their environment.